The Case for the Vaccine Passport - Maclure, Jocelyn; Bisson, Keven (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
In this critical commentary, we address the egalitarian critique according to which the use of a vaccine passport is unethical because it conflicts with the principle of equality, understood as requiring that citizens ought to be treated in the same way. We argue that this criticism is vulnerable to the levelling-down objection often addressed to some egalitarian theories. We add that the vaccine passport is morally justified if two minimal ethical conditions are satisfied: 1) it must be designed as a temporary and transitory public health restriction, and 2) the disparities of treatment it introduces ought to infringe as little as possible upon fundamental rights and should not negate access to essential public services.